GASTRONOMI SEBAGAI DAYA TARIK POTENSI WISATA KOTA PADANG PANJANG - Sari, Erlita; Mariya, Sri (JURNAL BUANA, 2024)
This research aims to determine 1) the analysis of the gastronomic potential, 2) the contribution of the government and 3) the distribution of gastronomy in the Padang Panjang City. This type of research is field research by taking the location of research in the culinary market and the long-distance city centre market using a qualitative approach. Padang Long has rich culinary potential, with some local culinaries such as Paragede Jaguang, Ampiang Dadiah, Tenong Bread, Darek Satay, Kapik Banana, Milk House, and Meatballs Amin become popular destinations. The Municipality of Padang Long has been actively engaged in promoting gastronomy by providing incentives in the gastronomy market to attract more visitors, offer cultural events, and encourage gastronomy entrepreneurs to participate in various promotional activities. Analysis of Gastronomy Data of Long Fields using ArcGIS with an average Nearest Neighbor Ratio of 0.838589 shows that the Long Field Special Culinary Food area is random. The gastronomic distribution of the city of Padang Panjang consists of 4 locations for Paragede Jaguang traders, 2 locations for Ampiang Dadiah traders, 1 location for Roti Tenong traders, 6 locations for Sate Darek traders in Padang Panjang, 2 locations for Amin Padang Panjang meatball traders, 1 Milk House trader Padang Panjang, 1 Kapik Banana trader, 2 Katupek Pitalah traders.